Unilateral Bimaxillary Idiopathic Fibrous Gingival Hyperplasia with Alveolar Bone Loss- Report of a Rare Case - R S Sathawane; R N Mody; Amit Parate (Wolters Kluwer Medknow Publications, 2007)
Gingival enlargements are of many types and vary according to the etiologic factors and pathologic processes that produce them. Though there are many classifications of gingival enlargement, the most practical one is as follows: 1) Inflammatory gingival enlargement 2) Fibrous gingival hyperplasia 3) Combination of inflammatory and fibrous hyperplasia. Gingival hyperplasia is a heterogeneous group of disorder, which appears clinically as diffuse, firm, and massive enlargement of the gingiva covering most of the crown of the teeth. Idiopathic gingival enlargement is a rare condition of undetermined etiology, although some cases have definite hereditary basis. A case of unilateral idiopathic fibrous gingival hyperplasia on left side of both the jaws with severe bone resorption is presented.